Respuesta :

[tex]g(p) \cdot h(p) = p^{4}+2 p^{3}-8 p^{2}-2p+4[/tex]

Solution:

Given data:

[tex]g(p)=(p-2)[/tex] and [tex]h(p)=\left(p^{3}+4 p^{2}-2\right)[/tex]

To find [tex]g(p) \cdot h(p)[/tex]:

[tex]g(p) \cdot h(p)= (p-2)\cdot \left(p^{3}+4 p^{2}-2\right)[/tex]

Distributive property: [tex]a(b+c)=ab + ac[/tex]

               [tex]= p\left(p^{3}+4 p^{2}-2\right) -2\left(p^{3}+4 p^{2}-2\right)[/tex]

               [tex]= \left(p^{4}+4 p^{3}-2p\right) +\left(-2p^{3}-8 p^{2}+4\right)[/tex]

               [tex]= p^{4}+4 p^{3}-2p-2p^{3}-8 p^{2}+4[/tex]

Arrange and add/subtract same powers.

              [tex]= p^{4}+(4 p^{3}-2p^{3})-8 p^{2}-2p+4[/tex]

               [tex]= p^{4}+2 p^{3}-8 p^{2}-2p+4[/tex]

Hence [tex]g(p) \cdot h(p) = p^{4}+2 p^{3}-8 p^{2}-2p+4[/tex]